Cloning and expression of the bovine cardiac sodium-calcium exchanger - Aceto,J.F.; Condrescu,M.; Kroupis, C.; Nelson,H.; Nelson,N.; Nicoll,D.; Philipson,K.D.; Reeves,J.P. (Arch.Biochem.Biophys., 1992)
Two clones (p17 and p13), each containing the complete coding sequence for the bovine cardiac Na+/Ca2+ exchanger, were obtained from a lambda gt10 cDNA library by screening with cDNA probes from the canine exchanger. The coding sequence of clone p17 was 92 and 98% identical to the canine cDNA at the nucleotide and amino acid levels, respectively. Nine of the 21 amino acid differences between the two exchangers were found within the 32-amino acid signal sequence. The sequenced portions of the 3' untranslated regions of the cow and dog clones were 88% identical. Na+/Ca2+ exchange activity was expressed in Xenopus laevis oocytes injected with cRNA from clone p17, and in COS cells transfected with expression vectors containing p17. Immunoprecipitation of 35S-labeled proteins from transfected cells with an antibody against the N-terminal portion of the bovine exchanger showed the presence of a 120-kDa protein corresponding to the intact cardiac exchanger. The second bovine clone (p13) did not express exchange activity in either of the above expression systems, presumably because it contained a 300-bp insert with multiple stop codons which interrupted the coding sequence. Comparison of the 5' untranslated regions of p13 and p17 revealed a 156-bp segment in p17 that was apparently spliced out of p13. This segment contained a short open reading frame. A chimera encoding the 5' untranslated region of p13 and the coding sequence of p17 exhibited only a modest (74%) increase in expressed exchange activity in transfected cells compared to p17, suggesting that the presence of the upstream open reading frame in p17 did not greatly reduce translation efficiency. The results suggest that alternate splicing mechanisms may be involved in processing mRNA for the bovine cardiac exchanger
Keywords: Amino Acid Sequence; Animals; Base Sequence; calcium; Carrier Proteins; Cattle; Cell Line; Cercopithecus aethiops; Cloning,Molecular; Codon; Dogs; Female; Gene Library; genetics; Introns; metabolism; Molecular Sequence Data; Myocardium; Oocytes; Plasmids; Restriction Mapping; Sequence Homology,Nucleic Acid; sodium; Sodium-Calcium Exchanger; Transfection; Xenopus laevis